Assessment of Impact of Artificial Intelligence on Curriculum Implementation in Tertiary Education, Nigeria (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This paper assessed the impact of artificial intelligence on curriculum implementation in tertiary institutions in Nigeria. The paper is a review paper. The paper used secondary data. The secondary data were collected from government documents, print resources and online publication. Inclusion and exclusion criteria were used to narrow the literature to the theme of the study. The paper concluded that artificial intelligence positively impacted curriculum implementation in tertiary institutions in Nigeria. Artificial intelligence aided effective teaching and research programme implementation in the tertiary institutions. Based on this findings, the paper recommends that government should increase funding of tertiary education in Nigeria. The budgetary allocation by the government should be increase in the tertiary institutions to enable the managers of the institutions to acquire more artificial intelligence facilities in their restive institutions.